Analytical Determination of Mechanical Characteristics of Asynchronous Motors by Varying the Electric Current Frequency - Buksnaitis, J. (Elektronika ir Elektrotechnika, 2011)
The analytical method for the determination of the mechanical characteristics of the asynchronous motors by varying the electric current frequency is analyzed. Not only the current frequency but also the supply voltage of the motor is changed in the frequency converters used to regulate the rotation speed of the asynchronous electric drives by using particular speed regulation law. The presented analytical method for the determination of mechanical characteristics is based on the same Kloss formulas which are dedicated to calculate the relative magnitudes of the torques under respective slips in the starting and operational parts of the mechanical characteristics and under nominal supply voltage parameters of the asynchronous motors. All the magnitudes included in these Kloss formulas (coefficients, exponent indexes, relative magnitudes of the starting and breakdown torques) are recalculated according to the modified parameters of the supply voltage and after that according to them the new relative magnitudes of the torques are determined under the selected slips. Using these relative magnitudes the families of the speed regulation mechanical characteristics of the asynchronous motors are determined. Ill. 2, bibl. 5, tabl. 4 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.433